1992
DOI: 10.1080/00207284.1992.11732578
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic Group Psychotherapy

Abstract: The author provides an overview of critical factors in the working phase of group psychotherapy from the perspective of psychodynamic theory. The discussion is organized around a clinical vignette to illustrate various types of intervention such as past, here and now, future; individual, interpersonal, group as a whole; in group--out of group; affect-cognition; and understanding--corrective emotional experience. The critical "windows into the unconscious," transference, counter-transference, and free associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 2 publications
0
30
0
1
Order By: Relevance
“…Rutan's psychodynamic model relies heavily on the principles of psychoanalytic theory (Rutan & Stone 1984, Rutan 1992). It assumes that maladaptive behaviours and beliefs are a result of unconscious drives and conflicts.…”
Section: Critique Of Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rutan's psychodynamic model relies heavily on the principles of psychoanalytic theory (Rutan & Stone 1984, Rutan 1992). It assumes that maladaptive behaviours and beliefs are a result of unconscious drives and conflicts.…”
Section: Critique Of Theoretical Modelsmentioning
confidence: 99%
“…It assumes that maladaptive behaviours and beliefs are a result of unconscious drives and conflicts. According to Rutan (1992, p. 20), the goal of therapy is ‘to help the patient gain awareness of those parts of the unconscious that result in destructive distortions in present‐day perceptions.’ Rutan adds that the therapist traditionally takes a very neutral, inactive stance, allowing free association among group members so that various unconscious projections, distortions and transference issues will inevitably come forward. Only then does a therapist make an interpretation to facilitate members’ consciousness of and ability to correct these maladaptive patterns.…”
Section: Critique Of Theoretical Modelsmentioning
confidence: 99%
“…Absorption may contribute to such experience through narrowing attentional focus (Butler, 2006) to the stimulating, corrective properties of interactions, to the relative attentional exclusion of group phenomena that are inessential to the client′s goals. Third, the client may utilise a heightened capacity for imaginative immersion to identify with the group overall, facilitating a positive internalisation of the group as a supportive and encouraging presence (Rutan et al, 2014). It may be that absorption contributes to clients feeling swept away by the interpersonal current of the group-as-a-whole, imagin- suggested that lower levels of the related five-factor personality trait openness to experience could map onto alexithymia, a constriction of emotional processing that has the potential to inhibit therapy (Ogrodniczuk, Piper, & Joyce, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how absorption might be intertwined with other aspects of clients′ difficulties-those in our study all suffered from personality dysfunction-and strengths. For example, it is possible that for some clients, absorption could have developed as a protective mechanism in the context of severe childhood abuse, as has been speculated regarding dissociation (Thomas, 2005 to absorption in relation to the group′s composition (Rutan et al, 2014). Clinicians′ awareness of absorption among group members, for example, might suggest that they foster, rather than interpretively inhibit, the initial development of idealised perceptions of the group experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation